Emerging trends in electrical, communications and information technologies : proceedings of ICECIT-2015 - Attele, Kapila Rohan; Amit Kumar (Science and Technology Information researcher); Sankar, V.; Rao, N. V.; Sarma, T. Hitendra (Springer, 2016)
This book includes the original, peer-reviewed research from the 2nd International Conference on Emerging Trends in Electrical, Communication and Information Technologies (ICECIT 2015), held in December, 2015 at Srinivasa Ramanujan Institute of Technology, Ananthapuramu, Andhra Pradesh, India. It covers the latest research trends or developments in areas of Electrical Engineering, Electronic and Communication Engineering, and Computer Science and Information.
Keywords: Computer science -- Congresses.; Artificial intelligence -- Congresses.; Image processing -- Digital techniques -- Congresses.; elektronické knihy; electronic books